Alignment of the Grade Nine Science and Technology Textbook with the National Curriculum - Yogi, Sundar Nath; Devkota, Balak (Educational Journal, 2026)
The alignment between textbooks and the national curriculum is essential for maintaining consistency, quality, and effectiveness in education despite of the central role of textbooks in classroom instruction. The alignment of the textbooks with the national curriculum often remains underexamined hence raising concerns about the consistency of envisioned learning outcomes. Hence this research was carried out to analyze the alignment of the textbook with the national curriculum in terms of objectives, content and methodology. Two documents i.e., Science and Technology curriculum and its text book developed by the Curriculum Development Center, Nepal were analyzed qualitatively through document analysis. For the analysis of the data, descriptive analysis and content analysis methods were used and then presented thematically. The result indicates that the text book is aligned with the objectives and content of the curriculum except some sequential misalliances. The curriculum objectives seem to be fulfilled but some objectives do not clearly define the content and number of objectives are not seen uniform with the ratio of teaching hours of the respective units. The strong student-centered pedagogical recommendation with activities and projects reflects foundation of the constructivist approach of the curriculum design. The finding of this research will contribute for the revision and improvement of curriculum and development of the aligned textbook. This study strongly recommends systematic revision of science textbooks to ensure full alignment with its national curriculum for effective pedagogical implementation and achieving learning outcomes. Moreover, related government agencies should focus on the alignment during the development of the textbooks.